Returns to education and the demand for labour in Vietnam - Seamus McGuinness; Elish Kelly; Pham Thi Thu Phuong; Ha Thi Thu Thuy (The Economic and Social Research Institute (ESRI), 2015)
Using data from the Vietnam Household Living Standards Survey, this paper examines the returns to education in Vietnam in 2002 and 2010, and how these returns changed over time. Given the economic growth that took place during this time period, the relative demand for labour is also assessed in order to identify if skill-biased technical change played a role in explaining the returns to education in Vietnam at a time of exceptional economic growth. The male and female education returns displayed a linear pattern in both 2002 and 2010, with earnings rising with increased levels of education. Relative to males with no qualifications, the returns to those with a vocational training qualification or below fell between 2002 and 2010, while the economic returns to a college education and above increased. Similar results were observed for females. In relation to relative labour demand, the results indicated that the demand for all levels of education (apart from males with a high school qualification) relative to those with no qualifications grew between 2002 and 2010. However, there was particularly strong growth in the demand for those with a vocational training qualification and above, especially an advanced degree qualification. Findings from the paper show that high levels of economic growth in Vietnam between 2002 and 2010 have facilitated increasing returns to education and demand for high skilled labour. In addition, there appears to be shortages for some types of skilled labour.
Keywords: 330